Correction to: Constructing mathematical bitterness scale related to teacher factor - Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto; Yanti (Jurnal Elemen)
Correction to: Jurnal Elemen, Vol. 10 No. 2, May 2024, p. 395-409